Compared physiological performances of Caulerpa prolifera and native seagrasses of Ria Formosa - Hofman, Jan Dirk (2021)
Seagrasses are among the most important and also mostly threatened ecosystems in the marine environment. Seagrass loss can occur in their competition with other macrophytes, like invasive macroalgae. These pose a serious threat and present numerous consequences to their new environment. Among those that can affect seagrasses, Caulerpa sp. are one of the most recognized genus. Different mechanisms can grant them a competitive advantage over seagrasses, resulting in partial or even complete replacement. Therefore, knowing how Caulerpa sp. functions and interacts with a new environment is crucial, especially in a system like Ria Formosa, where three of the four European seagrass species can be found. We aimed to study and compare different photo-physiological components of the subtidal seagrasses Cymodocea nodosa and Zostera marina and of the macroalgae Caulerpa prolifera along diel cycles, while at the same time identifying possible consequences of their interaction, using a mesocosm experiment. The first experiment was performed over the course of two days (48 hour cycle), collecting samples for biochemical analysis at pre-dawn and solar noon at the end. The mesocosm experiment involved planting Z. marina and C. prolifera separately and mixed. After 4 weeks, photosynthetic performance was tested using photosynthesis-irradiance curves and rapid light curves, and samples for biochemical analysis were collected. The seagrasses revealed higher effective quantum yield and non-photochemical quenching, mainly related to their xanthophyll pigments, while C. prolifera displayed a typical shade-adapted response. Furthermore, it displayed a different carbohydrate usage regime, which was related to its higher respiration rates. Although no different overall photosynthetic performance was detected in the interaction of the species, starch content in Z. marina rhizomes was significantly lower when C. prolifera was present. This work gives initial insight on the physiological performance of C. prolifera in Ria Formosa.